The Influence of Financial Knowledge and Financial Attitudes on Financial Management Behavior with Financial Self-Efficacy as an Intervening Variable - Putri Yasmin; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study aims to examine how understanding money and people's feelings about money affect how they manage their finances, with financial seIf-efficacy playing a key role in this process key factor in between, specifically among Generation Z and Millennials. The research used a quantitative causal design, and the total number of participants was 119, who were selected through an online survey method. Data analysis was done I used the StructuraI Equation ModeIing-PartiaI Least Squares (SEM-PLS) approach with the SmartPLS 4.0 software to analyze the data. From the testing of the structural model, it is clear that financiaI knowIedge, financiaI attitude, and financiaI seIf-efficacy all have a direct and important positive influence on financiaI management behavior. Financial self-efficacy might be an important link between financiaI knowledge and financial attitudes, which then affect how people manage their money.